The Effect of Letter Card Media on the Recognition of Capital Letters in Indonesian Language Lesson for Second Grade Students at SDN 01 Balai Karangan - Maria Marlina; Lilian Slow (Journal of General Education and Humanities, 2026)
Difficulties in recognizing capital letters persist among second-grade students, hindering early literacy development. This study aims to determine the effect of letter-card media on students’ ability to recognize capital letters at SDN 01 Balai Karangan. The research employed a quantitative approach using a one-group pretest-posttest design. The study subjects were 24 second-grade students. Data were collected through oral tests administered before and after the implementation of the letter-card media. The data analysis techniques included the Chi-square normality test and the Wilcoxon non-parametric test, as the post-test data were not normally distributed. The results indicated a significant improvement in students’ ability to recognize capital letters, as shown by all positive score differences and the Wilcoxon test results (T⁺ = 325, T⁻ = 0, T = 0). These findings demonstrate that letter-card media is effective in improving capital letter recognition among second-grade students.